2022
DOI: 10.1080/21655979.2022.2070996
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderic Acid A alleviates the degeneration of intervertebral disc via suppressing the activation of TLR4/NLRP3 signaling pathway

Abstract: As a multifactorial disease, intervertebral disc degeneration (IVDD) causes many spinal-related diseases, which causes disability in the workforce and heavy social costs all over the world. Recently, Ganoderic Acid A (GAA) has been reported to play many pharmacological effects. However, its effect on IVDD remains unclear. In the present study, our study determined that GAA significantly inhibited H 2 O 2 induced apoptosis, release of inflammatory cytokines and oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The activation of the TLR4/NLRP3 signaling axis could cause apoptosis, oxidative stress, and inflammatory responses in NP cells. It has been reported that the activation of the NF-κB/NLRP3 signaling pathway could decrease cellular functions of NP cells and promoted cell pyroptosis ( 27 ). NF-κB signaling activation improved NLRP3 inflammasome activity, and NLRP3 activation increased NF-κB signaling activation induced by TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the TLR4/NLRP3 signaling axis could cause apoptosis, oxidative stress, and inflammatory responses in NP cells. It has been reported that the activation of the NF-κB/NLRP3 signaling pathway could decrease cellular functions of NP cells and promoted cell pyroptosis ( 27 ). NF-κB signaling activation improved NLRP3 inflammasome activity, and NLRP3 activation increased NF-κB signaling activation induced by TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that activation of the TLR4/NLRP3 signaling pathway upregulates the expression of oxidative stress-related genes. Treatment with Ganoderic Acid A significantly upregulated ECM anabolic factors and inhibited the secretion of inflammatory factors and oxidative stress, thus protecting NPCs ( 57 ). Notably, Jacobsen et al recently altered the biomechanical properties of NPCs by attenuating actin alterations with the TLR4 inhibitor TAK-242, thereby attenuating inflammatory injury ( 58 ).…”
Section: Immunomodulation Associated With Ivddmentioning
confidence: 99%
“…In the H 2 O 2 -mediated-degeneration model, ganoderic acid significantly inhibited the expression of TLR4 and NLRP3. However, it still remains uncertain whether ganoderic acid directly acts on TLR4 or triggers the secondary reduction in TLR4 by scavenging H 2 O 2 [ 96 ]. In addition to H 2 O 2 , high-mobility group box-1 protein (HMGB1) and DAMPs also act on TLR4 receptors [ 97 ].…”
Section: Therapeutic Strategies Targeting Pyroptosis and Nlrp3 Inflam...mentioning
confidence: 99%